Weight regain after Roux-en-Y gastric bypass has a large negative impact on the Bariatric Quality of Life Index. Issue 1 (11th September 2017) - Jirapinyo, Pichamol; Abu Dayyeh, Barham K; Thompson, Christopher C
Abstract : Background: Despite initial successful weight loss, some patients may experience weight regain following Roux-en-Y gastric bypass (RYGB). Objective: To assess the impact of weight regain on bariatric patients' quality of life (QoL). Methods: This was a prospective cross-sectional study. Fifty-six consecutive RYGB patients were recruited and divided into weight-regain and weight-stable cohorts. QoL was assessed using the Bariatric Quality of Life (BQL) questionnaire. The BQL Index scores of the weight-regain and weight-stable groups were compared using Student's t -test. Additionally, the BQL Index score of the weight-regain group was compared with that of historical prebariatric patients. Predictors of BQL were assessed using univariate and multivariate linear regression analyses. Results: Of 56 RYGB patients, 41 (73%) had weight regain. On average, patients had body mass index (BMI) of 37 ±7.5 kg/m 2 and gained 34 ±26% of maximal weight initially lost. Weight-regain patients had lower BQL Index scores than weight-stable patients (44.8±6 vs 53±7, p<0.001). Patients with weight regain had similar BQL Index scores as the prebariatric patients despite lower BMI (BMI of 39.7±6.8 vs 47.2±7.6, p<0.05; BQL Index of 44.8±6 vs 41.6±10.4, p=0.144, respectively). Years from RYGB, BMI and amount of weight regain were associated with BQL Index on a univariate analysis (β=−0.55, −0.52, −0.7; p<0.0001). Only weight regain was a significant predictor of BQL on a multivariate analysis (β =−0.56; p=0.001). Conclusion: Weight regain had a negative impact on bariatric patients' QoL. Patients who regained at least 15% of maximal weight lost appeared to have as low QoL as those who had not undergone bariatric surgery despite a lower BMI.